Enteroinsular hormones in two siblings with Donohue syndrome and complete leptin deficiency. Issue 4 (11th December 2017) - Güemes, M; Rahman, SA; Shah, P; Hussain, K
Abstract : The main biochemical hallmark of the rare and lethal condition of Donohue syndrome (DS) is hyperinsulinemia. The roles of the gut and other pancreatic hormones involved in glucose metabolism, satiety and energy expenditure have not been previously reported in DS. Two siblings with genetically confirmed DS and extremely low weight underwent a mixed meal (MM) test where pancreatic hormones insulin, C‐peptide, glucagon, active amylin, pancreatic polypeptide (PP) as well as gut hormones active glucagon‐like peptide 1 (GLP‐1), glucose‐dependent insulinotropic peptide (GIP), ghrelin, peptide YY (PYY) and leptin were analyzed using a Multiplex assay. Results were compared to those of 2 pediatric controls. As expected, concentrations of insulin, C‐peptide and amylin were very high in DS cases. The serum glucagon concentration was undetectable at the time of hypoglycemia. GIPs concentrations were lower in the DS, however, this was not mimicked by the other incretin, GLP‐1. Ghrelin concentrations were mainly undetectable (<13.7 pg/mL) in all participants. DS cases had higher PYY and dampened PP concentrations. Leptin levels remained completely undetectable (<137.0 pg/mL). Patients with DS have extremely high amylin levels, completely undetectable serum glucagon and leptin levels with abnormal satiety regulating hormone PP with a relatively normal ghrelin response during a MM test. The low serum GIP might be acting as physiological brake on insulin secretion. The undetectable serum leptin levels suggest the potential of using leptin analogues as therapy for DS patients.